Nationwide surveillance of bacterial pathogens isolated from patients with acute uncomplicated cystitis in 2018: Conducted by the Japanese Research Group for Urinary Tract Infections (JRGU). Issue 8 (August 2021) - Wada, Koichiro; Yokoyama, Teruhiko; Uno, Satoshi; Araki, Motoo; Sadahira, Takuya; Maruyama, Yuki; Acosta, Herik; Nakajima, Hirochika; Hiyama, Yoshiki; Kunishima, Yasuharu; Togo, Yoshikazu; Nukaya, Takuhisa; et al.
Abstract: Introduction: The aim of this study was to monitor the development of drug-resistant bacteria isolated from acute uncomplicated cystitis (AUC) and to evaluate methodology of the survey conducted by collecting only clinical data. Methods: We enrolled female patients at least 16 years of age diagnosed with AUC in 2018. Patient information including age, menopausal status, and results of bacteriological examination were collected and analyzed regardless of bacterial identification, antimicrobial susceptibility testing or extended-spectrum β-lactamase (ESBL) detection method. Results: A total of 847 eligible cases were collected. Escherichia coli ( E. coli ) was the most frequently isolated bacterial species at about 70%, with proportions of fluoroquinolone-resistant E. coli (QREC) and ESBL-producing E. coli isolates at 15.6% and 9.5% of all E. coli isolates, respectively. The proportion of Staphylococcus saprophyticus ( S. saprophyticus ) was significantly higher in premenopausal women. Regarding the drug susceptibility of E. coli, isolates from Eastern Japan had significantly higher susceptibility to cefazolin, cefotiam and cefpodoxime and lower susceptibility to levofloxacin in postmenopausal women. ESBL-producing E. coli isolates had a high susceptibility to tazobactam-piperacillin, cefmetazole, carbapenems, aminoglycosides, and fosfomycin. In S. saprophyticus, the susceptibility to β-lactams including carbapenems was 40–60%. Conclusions: The proportions of QREC and ESBL-producing E. coli were increasing trends and lower susceptibility to LVFX in postmenopausal women was observed. Such surveillance, consisting of the collecting only clinical data, could be conducted easily and inexpensively. It is expected to be continuously performed as an alternative survey to conventional one collecting bacterial strains.